Thinking About the Past and Experiencing the Past - Debus, Dorothea (Mind & Language, 2013)
The present article aims to show that a subject can only fully grasp the concept of the past if she has some experiential, or recollective, memories of particular past events. More specifically, I argue that (1) in order for a subject to understand the concept of the past, it is necessary that the subject understand the concept of a particular past event in such a way that it might contribute to her understanding of the concept of the past. (2) But then, in order for a subject to understand the concept of a particular past event in such a way that it might contribute to her understanding of the concept of the past, it is necessary that the subject have some recollective memories of particular past events. (C) Hence, a subject can only understand the concept of the past if she has some recollective memories of particular past events. I defend the premises of the present argument against various objections, indicate why we should accept both premises, and accordingly end by endorsing the argument's conclusion. © 2013 Blackwell Publishing Ltd.
CRIS-Team Scopus Importer:2024-10-02